Responses of hematological parameters and aerobic performance of elite men and women swimmers during a 14-week training program - Santhiago, Vanessa [UNESP] (2009)
Santhiago, V, da Silva, ASR, Papoti, M, and Gobatto, CA. Responses of hematological parameters and aerobic performance of elite men and women swimmers during a 14-week training program. J Strength Cond Res 23(4): 1097-1105, 2009-The main purpose of the present investigation was to verify the responses of hematological parameters in men and women competitive swimmers during a 14-week training program. Twenty-three Olympic and international athletes were evaluated 4 times during the experiment: at the beginning of the endurance training phase (T1), at the end of the endurance training phase (T2), at the end of the quality phases (T3), and at the end of the taper period (T4). On the first day at 8:00 AM, each swimmer had a blood sample taken for the determination of hematological parameters. At 3:00 PM, the athletes had their aerobic performance measured by anaerobic threshold. On the second day at 8:00 AM, the swimmers had their aerobic performance measured by critical velocity. Hematocrit and mean corpuscular volume diminished (p ≤ 0.05) from T1 to T2 (men: 5.8 and 7.2%; women: 11.6 and 6.8%), and increased (p ≤ 0.05) from T2 to T3 (men: 7.2 and 6.0%; women: 7.4 and 5.2%). These results were related to the plasma volume changes of the athletes. However, these alterations do not seem to affect the swimmers' aerobic performance. For practical applications, time-trial performance is better than aerobic performance (i.e., anaerobic threshold and critical velocity) for monitoring training adaptations. © 2009 National Strength and Conditioning Association.